Beyond adoption: The persistence of conservation and climate-smart agricultural practices in the United States - Paul J. Ferraro; Maria Bowman; Hannah E. Correia; Jing Gao; Kelsey R. Larson; Kent D. Messer; Laura A. Paul; Bryan Pratt; Linda S. Prokopy (Proceedings of the National Academy of Sciences, 2025)
Achieving sustainability goals requires that humans change their behavior not just once but persistently. Yet despite decades of research on the adoption of conservation and climate-smart agricultural practices, little is known about the extent to which these practices persist over time. One key reason is the lack of longitudinal, field-level data. Using ground-verified, longitudinal data on cover cropping across thousands of farm parcels in Indiana (USA), we find that persistence is low and contrasts sharply with the predictions made by Indiana conservation experts. We also find low persistence in a new national dataset of self-reported cover cropping by farm operators. The potential for low behavioral persistence in sustainable agricultural practices raises essential questions about the design of conservation programs and the modeling and valuation of ecosystem services.